2017
DOI: 10.1111/ijcs.12393
|View full text |Cite
|
Sign up to set email alerts
|

Second‐hand clothing consumption: A generational cohort analysis of the Chinese market

Abstract: China's rapidly growing economy and consumption are creating serious environmental problems in the country. The throwaway trend credited to fast fashion changes and short-lived styles made textiles and clothing a new body of solid wastes, resulting in a negative environmental consequence in China. While minimizing consumption of textiles and apparel cannot be the primary solution to environmental problems, it is important to enhance consumer awareness of the impact of their daily consumption on the environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(96 citation statements)
references
References 22 publications
(29 reference statements)
6
88
1
1
Order By: Relevance
“…In the studies conducted on Chinese consumers, three main variables influencing the intention behind second-hand clothing use were taken into account: perceived values (hedonic, economic, environmental, and uniqueness), perceived concerns, and perceived descriptive norms. The obtained results varied for four generational cohorts; the youngest respondents (post-1990s) were found to be the most willing to consume second-hand clothing and at the same time were the only group whose intention to buy was influenced by perceived economic value [5]. Additionally, some other previous studies showed that economic reasons (price sensitivity and frugality) has a big influence on SHB intention [12,13,18,19].…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…In the studies conducted on Chinese consumers, three main variables influencing the intention behind second-hand clothing use were taken into account: perceived values (hedonic, economic, environmental, and uniqueness), perceived concerns, and perceived descriptive norms. The obtained results varied for four generational cohorts; the youngest respondents (post-1990s) were found to be the most willing to consume second-hand clothing and at the same time were the only group whose intention to buy was influenced by perceived economic value [5]. Additionally, some other previous studies showed that economic reasons (price sensitivity and frugality) has a big influence on SHB intention [12,13,18,19].…”
Section: Introductionmentioning
confidence: 83%
“…And it is quite a special manifestation of consumption reduction that was not taken into account among environmentally-motivated consumption reduction [44] or climate mitigating actions [45]. SHP may be recognized as an activity negatively influencing perceived social status [5,18,19] so further research on attitudes, social norms (both injunctive and descriptive), intentions, and SHP behavior, depending on the culture of the country, is necessary in order to deepen the knowledge of other aspects of self-limiting behavior and to design campaigns that effectively promote desirable, pro-environmental behavior. AOR3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are various alternatives to the classic form of collaboration including swapping, renting and purchasing second-hand fashion. In regards to this systematic review, several scholars had specifically touched on collaboration in terms of clothing and discovered the level of acceptance in China, United States, Iran, and German (Iran et al, 2019;Liang & Xu, 2018;Norum & Norton, 2017). Based on the research by Iran et al (2019), Germany students were more engaged in collaborative fashion compared to the students in Iran.…”
Section: Collaborative Fashionmentioning
confidence: 99%